PELATIHAN INSEMINASI BUATAN PADA TERNAK BABI DI DENPASAR SELATAN - K, BUDAARSA.; MARIANI, N. P.; SURYANI, N.; BUDIASA, I.K.MANGKU (Buletin Udayana Mengabdi; Vol 8 No 1 (2009): Volume 8 No.1 – April 2009, 2012)
ABSTRACT The short cource of artifcial insemination on pig was conducted on September 13th. 2008. at South Denpasar. There are 18 Postgraduates of Faculty of Animal Husbandry Udayana University as participants of this activity. The aimed of this activity was increasing knowledge and skill of participants to collect and process the semen of pig until ready to be used on insemination. The method of activity was giving knowledge especially on technology in pig artificial insemination and practices in field. Based on the process of short course it can be concluded that, the response of participants on artificial insemination was excelent. This short course improved the knowledge and skill of artificial insemination of the participants and then practiced inseminate on 10 of sows.